Orchid re-introductions: an evaluation of success and ecological considerations using key comparative studies from Australia - Reiter, N.; Whitfield, J.; Pollard, G.; Bedggood, W.; Argall, M.; Dixon, Kingsley; Davis, B.; Swarts, N. (Springer Netherlands, 2016)
With global biodiversity in decline, there is now an urgent requirement to take ameliorative action for endangered species in the form of reintroductions. For the highly diverse orchid family, many species face imminent extinction. Successful reintroductions that result in self-sustaining populations require not only an understanding of existing threats, but an in-depth understanding of species ecology. Increasingly, translocations, ranging from re-introductions to assisted colonisation, are being adopted as recovery actions. Do these translocations mitigate threatening processes and account for the two key ecological attributes for orchid survival; pollinator and mycorrhizal presence? Here, we conducted a literature review identifying the known threats to orchid survival and their necessary mitigation strategies. Next, we evaluated the success of 74 published international orchid translocations on 66 species against a consideration of orchid ecological attributes. Lastly, we empirically tested an additional 22 previously unpublished re-introductions on 12 species undertaken since 2007 against a re-introduction process that accounts for identified threats and orchid ecological attributes. We identified habitat destruction, weed invasion, herbivory, illegal collection, pollinator decline, pathogens and climate change as critical threats to orchid survival. In our global review based on published translocations, the average survival rate, 1-year post translocation was 66 % yet only 2.8 % of studies reported natural recruitment in field sites. Although survival of translocated orchids is clearly being achieved, these programmes did not relate orchid growth and development to key ecological requirements of orchid population resilience, pollinator and mycorrhizal ecology. Ensuring pollinator and mycorrhizal presence shows that these two factors alone are key factors influencing survival and persistence in an Australian review of 22 previously unpublished orchid re-introductions. In the Australian review flowering in the year following, out-planting was observed for 81 % of the re-introductions with seed set occurring in 63 % of re-introductions within the length of the study. Recruitment was observed in 18 % of the Australian re-introduced populations indicating a degree of population resilience. As orchid re-introductions will be a major strategy for wild orchid conservation in the future, we present a framework for orchid re-introductions, including criteria for success. We recommend symbiotic propagation and, for specialised pollination syndromes, the study of pollinator interactions prior to site selection and re-introduction of plants.